Internal consistency, price rigidity and the microfoundations of macroeconomics. - Wren-Lewis, S (Taylor and Francis, 2011)
Macromodels based on microfoundations represent the dominant approach in macroeconomics. These models appear to adopt a clear methodological approach, which promotes internal consistency above external consistency as a necessary condition of admissibility. This paper develops two arguments. The first is that internal consistency makes the development of microfounded macromodels dependent on the pace of theoretical innovation. This had led to an internal debate between ‘pragmatists’ who argue for limited departures from internal consistency, and ‘purists’ who claim that this would compromise methodological integrity. The second argument is directly relevant to this debate. It is that the inclusion of price rigidity into these models via short-cuts like Calvo contracts has required a key modification of the microfoundations methodology, such that internal consistency can only be claimed indirectly by appeal to theory developed elsewhere. This modification has repercussions that imply that the microfoundations project is not as unblemished as the ‘purists’ imagine.